The affection of fine bubbles (FBs) aplication on growth, feed efficiency of striped catfish, Pangasianodon hypophthalmus (Sauvage, 1878) and water quality in aquaponic system - Yuli Andriani; Zahidah Zahidah; Rosidah Rosidah; Iskandar Iskandar (Jurnal Iktiologi Indonesia, 2021)
This research aims to determine the effect of fine bubble technology with different pressures on Siamese catfish seed's growth and feed efficiency in an aquaponic system. This research used a completely randomized design with four treatments and three replications. Treatment A (Control), Treatment B (FBs with a pressure of 4.5 atm), Treatment C (FBs with a pressure of 5 atm and treatment D (FBs with a pressure of 5.5 atm). The parameters observed were Specific Growth Rate, Feed Conversion Ratio, water quality (temperature, pH, DO, and ammonia), and plant productivity. The seeds used were catfish seeds aged 16-36 days, 1-2 inches long, and weighed 0.26-0.29 grams. The container used is a fiber tub of 16 units with a size of 70 cm x 70cm x 70 cm. The feed used is commercial feed PF 1000 content crude protein 35%. The data were analyzed using variance with the F test at the 95% confidence level. The best treatment for catfish growth was treatment D (pressure 5.5 atm), which gave the highest SGR value of 7.24 ± 0.5 and FCR value of 1.19 ± 0.09. The value of water quality parameters is in suitable condition for the growth of catfish seed. The best plant productivity was found in treatment D with an average weight of 60.75 g. Abstrak Penelitian ini bertujuan untuk menentukan pengaruh teknologi fine bubble dengan tekanan yang berbeda terhadap pertumbuhan dan efisiensi pakan benih ikan patin siam dalam sistem akuaponik. Penelitian ini menggunakan Rancangan Acak Lengkap dengan empat perlakuan dan tiga ulangan. Perlakuan A (Kontrol), Perlakuan B (FBs dengan tekanan 4,5 atm), Perlakuan C (FBs dengan tekanan 5 atm) dan perlakuan D (FBs dengan tekanan 5,5 atm). Parameter yang diamati berupa laju pertumbuhan spesifik (LPS), nisbah konversi pakan (NKP), kualitas air (suhu, pH, oksigen terlarut, dan ammonia) dan bobot rata-rata tanaman. Benih yang digunakan adalah benih ikan patin dengan umur 16-36 hari, panjang 1-2 inci dan bobot 0,26-0,29 gram. Wadah yang digunakan adalah bak fiber sebanyak 16 buah unit dengan ukuran 70 cm x 70cm x 70 cm. Pakan yang digunakan adalah pakan komersial PF 1000 dengan kandungan protein kasar 35%. Data dianalisis menggunakan sidik ragam dengan uji F pada taraf kepercayaan 95%. Perlakuan terbaik terhadap pertumbuhan ikan patin adalah perlakuan D (tekanan 5,5 atm), yang memberikan nilai LPS tertinggi sebesar 7,24 ± 0,5% dan NKP sebesar 1,19 ±0,09. Nilai parameter kualitas air berada dalam kisaran yang layak untuk mendukung pertumbuhan benih ikan patin. Produktivitas tanaman terbaik terdapat pada perlakuan D dengan bobot rata-rata tanaman kangkung sebesar 60,75 gram.